Microwave-Assisted Deep Eutectic Solvent Extraction, Structural Characteristics, and Biological Functions of Polysaccharides from Sweet Tea (Lithocarpus litseifolius) Leaves - Ding-Tao Wu; Meng-Xi Fu; Huan Guo; Yi-Chen Hu; Xiao-Qin Zheng; Ren-You Gan; Liang Zou (MDPI AG, 2022)
The leaf of sweet tea (Lithocarpus litseifolius) is widely used as an edible and medicinal plant in China, which is rich in bioactive polysaccharides. In order to explore and promote the application of sweet tea polysaccharides in the functional food industry, the microwave-assisted deep eutectic solvent extraction (MDAE) of polysaccharides from sweet tea leaves was optimized, and the structural properties and biological functions of sweet tea polysaccharides prepared by MDAE (P-DM) were investigated and compared with that of hot water extraction (P-W). The maximum yield (4.16% ± 0.09%, w/w) of P-DM was obtained under the optimal extraction conditions (extraction time of 11.0 min, extraction power of 576.0 W, water content in deep eutectic solvent of 21.0%, and liquid-solid ratio of 29.0 mL/g). Additionally, P-DM and P-W possessed similar constituent monosaccharides and glycosidic bonds, and the homogalacturonan (HG) and arabinogalactan (AG) might exist in both P-DM and P-W. Notably, the lower molecular weight, higher content of total uronic acids, and higher content of conjugated polyphenols were observed in P-DW compared to P-W, which might contribute to its much stronger in vitro antioxidant, anti-diabetic, antiglycation, and prebiotic effects. Besides, both P-DW and P-W exhibited remarkable in vitro immunostimulatory effects. The findings from the present study indicate that the MDAE has good potential to be used for efficient extraction of bioactive polysaccharides from sweet tea leaves and P-DM can be developed as functional food ingredients in the food industry.